Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ejlt.201700236
|View full text |Cite
|
Sign up to set email alerts
|

Olive Pomace in Diet Limits Lipid Peroxidation of Sausages from Cinta Senese Swine

Abstract: In order to examine whether olive pomace (OP), the mean by-product of olive oil extraction, can be included in the animal diet, its effect on the raw mixture and sausages made from meat from OP-fed Cinta Senese swine is tested by comparing it with a diet supplemented with high oleic sunflower oil (SO) and a control diet (C). Proximate composition, pH, color, total culturable bacteria, lactic acid bacteria (LAB), and lipid oxidation are evaluated in both the raw mixture and sausages. The aroma profile is also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…Differences in carcass fat content are expected when pigs consume more energy than required with high-energy diets or when the indispensable amino acid or protein levels in diets are lower than required (Cámara et al 2016). With respect to meat quality traits, Serra et al (2018) showed similar pH levels and lower yellowness (b*) with the inclusion of olive pomace in pig diets. Despite this our results are in accordance with those authors, only the pH values were affected by feeding OC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in carcass fat content are expected when pigs consume more energy than required with high-energy diets or when the indispensable amino acid or protein levels in diets are lower than required (Cámara et al 2016). With respect to meat quality traits, Serra et al (2018) showed similar pH levels and lower yellowness (b*) with the inclusion of olive pomace in pig diets. Despite this our results are in accordance with those authors, only the pH values were affected by feeding OC.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were caused by the oleic acid increment in the diet, since the deposition of FA in pigs is known to be primarily influenced by the FA composition of the diet (Cava et al 1997). The modification of FA profile with the addition of olive by-products has been described by numerous authors (González et al, 2012;Joven et al, 2014;Serra et al, 2018), being of interest due to the improved sensory quality of meat.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, the effects of olive by‐products have been recently tested. The dietary inclusion of 25% of olive pomace reduced lipid oxidation in sausages, 11 whereas other authors using 5% of olive pulp did not find clear effects on antioxidant capacity 12 . The specific incorporation of pure oleuropein extract in a previous study showed clear effects in pigs in vivo prior to slaughter with changes in the antioxidant status and plasma antioxidant amino‐acids 13 .…”
Section: Introductionmentioning
confidence: 92%
“…Additionally OP polar lipids possess in vivo anti‐atherogenic properties . There are limited scientific data on broilers compounded feed enrichment with olive oil production by‐products such as olive pulp, whereas OP inclusion in animal feeds (such as lamb, goat, and rabbit feeds), cattle feeds, swine feeds, and fish feeds is more common. Taken into consideration the functional properties of OP, the aim of the present study was to expand our previous work on olive pomace and fish feeds and to evaluate the potential dietary inclusion of OP in broiler diet by assessing broilers growth performance and the nutritional value of the obtained meat by assessing its in vitro antithrombotic properties and organoleptic characteristics.…”
Section: Introductionmentioning
confidence: 99%